Halal Tourism Governance Based on the Fatwa of the National Sharia Council on Tourism Improvement - BAHRUDIN, Moh. (Journal of Environmental Management and Tourism, 2022)
This study aims to determine the governance of halal tourism in Lampung based on the Fatwa of the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI) No 108/DSN-MUI/X/2016 concerning Tourism Improvement. The research method uses an empirical qualitative approach, as well as legal and doctrinal approaches. Data collection methods include observation, interviews, and literature study. The results of the analysis reveal two things. First, the management of halal tourism based on the DSN-MUI Fatwa consists of 11 (eleven) general provisions and 15 (fifteen) definitions. Four objects are the focus of general provisions, namely tourism, sharia tourism, tourism, and sharia tourist destinations. There are six subjects, namely tourists, sharia travel agencies, tour guides, tourism entrepreneurs, and therapists. Second, the implementation of the concept of Halal Tourism Governance towards increasing Sharia Tourism in Lampung is realized in five components. It can be concluded that the management of halal tourism and its implementation cannot be separated from the sources of fiqh law (ushul al-fiqh). The implication highlights the importance of central and local government efforts to encourage the development of laws on effective halal tourism governance. The private sector and the public as actors in the halal tourism industry must pay attention to the DSN MUI fatwa. So, halal tourism can make a significant contribution to the welfare of the community, especially in Lampung Province.